Senam Seribu Learning with Audio Visual Media - Yogi Slamet; Entan Saptani; Respaty Mulyanto (Universitas Pendidikan Indonesia, 2023)
In this study, it began with the findings in the field of learning rhythmic gymnastics where it was found that students had less mastery of movements, lack of completeness of movements with rhythm, and students did not memorize the movements of the thousand gymnastics. The application of audio-visual media can help students memorize the thousand gymnastics movements, the suitability of the movements with the rhythm of the music, the teacher is less creative in utilizing the available facilities and infrastructure, students are less enthusiastic in participating in learning. The aim of the researcher is to determine the application of audio-visual media to improve the learning of a thousand gymnastics “new Indonesian fun gymnastics”. The research method used by researchers is literature study, with designs ranging from collecting sources, analysis and conclusions. The results of this study are in the form of predictions about the improvement of learning exercise in a senam seribu.